Pluralismo religioso e scuola pubblica in Italia: spazi per l'inclusione e questioni aperte - Carla Roverselli (LED Edizioni Universitarie, 2019)
In Italy, alongside the Catholicism of the majority, there are more and more forms of religious diversity that indicate an evident change in socio-religious geography of our country. The presence of minority religions on the public scene immediately calls into question the role that schools can and must play in the formation of citizens and therefore reopen the debate, never closed, of religious education within the school. The latter is an important sign of the school's ability to form cultural pluralism. In fact we must be aware of the fact that religious illiteracy hinders the construction of a culture of responsible citizenship and produces a democratic illiteracy. This article presents what the Italian public school is trying to do to promote religious pluralism in teaching but also the obstacles to these efforts. In particular, it will be considered the management that public school makes of that particular space that is the hour of «alternative activities».